Management of bleeding in severe factor V deficiency with a factor V inhibitor. Issue 1 (12th February 2014) - Ardillon, L.; Lefrançois, A.; Graveleau, J.; Fouassier, M.; Ternisien, C.; Sigaud, M.; Fretigny, M.; Archambeaud, I.; Trossaërt, M.
<x xml:space="preserve">Abstract</x> Factor V (FV) inhibitor arises rarely after using fresh frozen plasma (FFP) to treat inherited FV deficiency and is often a real therapeutic challenge. Here, we report a patient with a severe FV deficiency who developed such an inhibitor and was then treated with recombinant activated FVII (rFVIIa) and platelet concentrates (PC). Monitoring was assessed by thrombin generation assay (TGA). PC were more effective than rFVIIa in treating bleeding, but there was no correlation between the TGA results and clinical efficacy.